Zero Waste Store: A Way to Promote Environment-friendly Living - Belen E. Bagui; Louise Rey Angeli C. Arellano (CV. Literasi Indonesia, 2021)
This study focuses on the emergence of Zero Waste Store: A Way to Promote Environmental-Friendly Living. The principle behind zero waste is to reduce the environmental pollution that decomposes less decomposes. Waste management begins with waste prevention and continues with waste sorting, producer accountability and waste charges based on the amount of waste disposed of the implementation variable of zero waste is community waste management and the lack of resources and government subsidies. Throughout the study, the perceptions, adaptation, and promotion about zero waste store as an eco-friendly and plastic-free environment. The researchers used a phenomenological qualitative research design, in which the researchers set aside both perceptions and biases to completely comprehend the respondents' perspectives and lives. The study was conducted using Google forms as the platform of the questionnaire. The participants of this study are five (5) sari-sari store owners residing around the area of Batangas City. Implementing Zero Waste Store can benefit the reduction of plastic pollution that occurs to our environment both inland and water. The zero-waste store must be implemented in different places to gradually reduce the usage of plastic and trash in our households.